Characteristics of alcohol recovery narratives: Systematic review and narrative synthesis. - Mohsan Subhani; Usman Talat; Holly Knight; Joanne R Morling; Katy A Jones; Guruprasad P Aithal; Stephen D Ryder; Joy Llewellyn-Beardsley; Stefan Rennick-Egglestone (PLoS ONE, 2022)
Background and aims Narratives of recovery from alcohol misuse have been analysed in a range of research studies. This paper aims to produce a conceptual framework describing the characteristics of alcohol misuse recovery narratives that are in the research literature, to inform the development of research, policy, and practice. Methods Systematic review was conducted following PRISMA guidelines. Electronic searches of databases (Ovid MEDLINE, EMBASE, CINHAL, PsychInfo, AMED and SCOPUS), grey literature, and citation searches for included studies were conducted. Alcohol recovery narratives were defined as "first-person lived experience accounts, which includes elements of adversity, struggle, strength, success, and survival related to alcohol misuse, and refer to events or actions over a period of time". Frameworks were synthesised using a three-stage process. Sub-group analyses were conducted on studies presenting analyses of narratives with specific genders, ages, sexualities, ethnicities, and dual diagnosis. The review was prospectively registered (PROSPERO CRD42021235176). Results 32 studies were included (29 qualitative, 3 mixed-methods, 1055 participants, age range 17-82years, 52.6% male, 46.4% female). Most were conducted in the United States (n = 15) and Europe (n = 11). No included studies analysed recovery narratives from lower income countries. Treatment settings included Alcoholic Anonymous (n = 12 studies), other formal treatment, and 'natural recovery'. Eight principle narrative dimensions were identified (genre, identity, recovery setting, drinking trajectory, drinking behaviours, stages, spirituality and religion, and recovery experience) each with types and subtypes. All dimensions were present in most subgroups. Shame was a prominent theme for female narrators, lack of sense of belonging and spirituality were prominent for LGBTQ+ narrators, and alienation and inequality were prominent for indigenous narrators. Conclusions Review provides characteristics of alcohol recovery narratives, with implications for both research and healthcare practice. It demonstrated knowledge gaps in relation to alcohol recovery narratives of people living in lower income countries, or those who recovered outside of mainstream services. Protocol registration Prospero registration number: CRD42020164185.